Letter
016a-0026-001 UNIÓ CATALANA PRO SOCIETAT DE LES NACIONS UNION CATALANE POUR LA S.D.N. CATALAN LEAGUE OF NATIONS UNION BARCELONA CASP. 26 Gentlemen We are happy to send you, under the same cover, a copy of the request we addressed to the Government of Catalonia, with the aim of hinting to them the creation of a Centre of International Research into the social transformation in Spain, under the patronage of the League of Nations. We hope that this initiative will deserve the approval of the Catalan Government, and that, in this case, your sympathetic support would increase our chances of getting a favourable reception on the part of the Secretaryship of the League of Nations. We are Yours sincerely [signature] UNIO CATALANA PRO S.D.N. Cir. N. 1 292/946/16a/28